2006
DOI: 10.1248/bpb.29.811
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Central Activity of Hydroxydihydrocarvone

Abstract: The central effects of hydroxydihydrocarvone (HC), an analogue of several monoterpenes, were evaluated in animal models. General behavior, locomotor activity, pentobarbital-induced sleeping time, pentylenetetrazol (PTZ)-induced convulsions, and acetic acid-induced writhing were evaluated in mice. The compound caused palpebral ptosis, decreased the response to touch, and increased sedation (general behavioral profile). HC (50-200 mg/kg) caused a significant dose-dependent decrease in the spontaneous motor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…Recently, various studies have shown that monoterpenes and their derivative compounds also exhibit several types of pharmacological properties, such as antinociception and sedation (Santos & Rao, 2000;Galeotti et al, 2002;De Sousa et al, 2006a, 2007b. In this regard, the aim of the present study was to evaluate the CNS depressant properties and antinociceptive potential of CTL in mice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, various studies have shown that monoterpenes and their derivative compounds also exhibit several types of pharmacological properties, such as antinociception and sedation (Santos & Rao, 2000;Galeotti et al, 2002;De Sousa et al, 2006a, 2007b. In this regard, the aim of the present study was to evaluate the CNS depressant properties and antinociceptive potential of CTL in mice.…”
Section: Discussionmentioning
confidence: 98%
“…They are found in edible as well as medicinal plants with a therapeutic property (Carneiro et al, 1997). Additionally, monoterpenes and their derivative compounds exhibit several types of pharmacological properties, such as anxiolytic (Silva et al, 2007), antinociceptive (De Sousa et al, 2007b), sedative (Elisabetsky et al, 1995;De Sousa et al, 2006a, 2007a, antidepressant (De Sousa et al, 2006b), and anticonvulsant (Viana et al, 2000;De Sousa et al, 2006c, 2007c. In this regard, citronellal (3,7-dimethyl-6-octen-1-al) as a monoterpene is a major component of the essential oils in various aromatic species, such as Cymbopogon winterianus Jowitt (Java citronella) (Quintans-Júnior et al, 2008), Corymbia citriodora (Hook.)…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that some monoterpenes present in many essential oils possess pharmacological properties, such as anticonvulsant (De Sousa et al, 2007a, 2006a), analgesic (Gonçalves et al, 2008Amaral et al, 2007;De Sousa et al, 2007b), sedative (De Sousa et al, 2007c) and anxiolytic-like (Silva et al, 2007) activity in animal experiments. Recently, we demonstrated that derivatives of monoterpenes also exhibit several types of pharmacological properties, such as antinociceptive De Sousa et al, 2004), sedative (De Sousa et al, 2006b) and antidepressant (De Sousa et al, 2006c). The essential oil of the plant Mentha ¥ villosa Hudson (Lamiaceae), popularly known as "hortelã -da-folha-miú da", has shown a central nervous system-depressant effect (Raya et al, 1990) (Guedes et al, 2004), antinociceptive (De Sousa et al, 2007b) and relaxant of intestinal smooth muscle (Sousa et al, 1997) effects.…”
Section: Introductionmentioning
confidence: 99%
“…1) found as the main active component of spearmint oil (Mentha spicata), a relative of common mint distilled from this plant. 8,9) Recently, our group has demonstrated that (Ϫ)-carvone derivatives, such as rotundifolone, 10) hydroxydihydrocarvone, 11) and epoxy-carvone 12) appear to have analgesic properties. Such compounds decreased the writhing nociceptive response induced by acetic acid in mice, 10,11) although the mechanisms underlying such properties remain unclear.…”
mentioning
confidence: 99%